Analisis Tingkat Kepuasan Pelanggan Perusahaan Daerah Air Minum Kabupaten Majalengka - Herdiana, Deni; Sulaksana, Jaka (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
The purpose of this study was to determine the level of community satisfaction with PDAM Majalengka Regency and to determine the service quality of PDAM Majalengka Regency. Measurement of the Community Satisfaction Index and the quality of PDAM Majalengka Regency public services is carried out by distributing questionnaires to PDAM customers. The sampling method used is incidental sampling, namely determining the sample by "coincidence", that is, anyone who coincidentally meets the researcher can be used as a sample. The highest average value per service element is the courtesy and friendliness of the service staff, while the lowest average value per service element is the discipline of the service staff. Service unit performance at PDAM Majalengka Regency“good” because the value is between 76.61-88.30 which is in service quality B (good). Indicators that can be categorized as in accordance with community expectations are: (1) Politeness and Friendliness of Service Officers; (2) Certainty of Service Fees; (3) The reasonableness of the fee to get the service; and, (4) the accuracy of the implementation of the service time schedule; (5) Environmental Comfort; (6) Service Security. Meanwhile, indicators that are still below the average conformity level are: (1) Understanding of the ease of service procedures for PDAM Majalengka; (2) Terms of Service; (3) Capability of PDAM Majalengka service staff; (4) Fairness to get service (5) Speed of service (6) Clarity and certainty of serving officers; (7) Discipline of officers in providing services; (8) Responsibilities of officers in providing services.